The Influence of Using Youtube Media Regarding Units of Length on Learning Outcomes in Second Grade of Mathematics Learning at Madrasah Ibtidaiyah Pager Semarang - Fista Sixnori; Praptiningsih; M. Fatchurrohman (CV. Creative Tugu Pena, 2024)
The objectives of this research are to find out the application of YouTube media learning in mathematics subjects about units of length for class 2 students, to improve learning outcomes in mathematics subjects about units of length by using YouTube media learning media for two class grades, and to find out how effective the use of YouTube media is in mathematics subjects regarding length units for grade two students at Madrasah Ibtidaiyah Pager Kaliwungu, Semarang. This research method uses a quantitative approach. The population in this study was two class of Madrasah Ibtidaiyah Pager, Kaliwungu, Semarang, 37 students. This research was conducted at Madrasah Ibtidaiyah Pager by taking samples using a total sampling of 37 students. Data collection used observation, questionnaires and documentation. The results of this research show : First, The results of using media youtube produced the highest score of 80 and the lowest score of 37 from 37 class II students with 6 students in the very high category, 13 students in the high category, 12 students in the low category and 4 students in the very low category. Second, The learning outcomes produced the highest score of 90 and the lowest score of 75, while the mean was 81.75676 with a standard deviation of 4.323. that the results from the YouTube media were 9 students in the very high category, 8 students in the high category, 14 students in the low category and 6 students in the very low category. Third youtube learning media has an effect on student learning outcomes by 0.776. This is because it has a sig value of 0.000 or <0.05. Thus, increasing youtube learning media will increase student learning outcomes by 77.6%.